FAT INTAKE, NATRIUM INTAKE, AND SLEEP DURATION ARE STRONGLY ASSOCIATED WITH PRE-METABOLIC SYNDROME IN ADOLESCENTS - Farah Nuriannisa; Pratiwi Hariyani Putri; Sa'bania Hari Raharjeng; Catur Wulandari (The Indonesian Journal of Public Health, 2025)
Introduction: The prevalence of pre-metabolic syndrome components, such as abdominal obesity and elevated blood pressure, in teenagers is increasing yearly. One of the modifiable risk factors to pre-metabolic syndrome is lifestyle, including dietary intake, physical activity, and sleep duration. Based on preliminary study, 80% (12 of 15) students were found to have high blood pressure. Aims: The objective of this study was to evaluate the relationship between nutrition and lifestyle factors with pre-metabolic syndrome in high school students. Methods: This study was cross-sectional design with 90 adolescents as respondents. Instruments used in this study were sphygmomanometer and waist ruler to measure blood pressure and waist circumference; 3x24 hours of food record and SQ-FFQ to observe dietary intake; modified PSQI to assess sleep duration; and modified IPAQ to know physical activity score in respondents. All data were statistically analyzed with Spearman correlation test. Results: The findings of this study were fat intake, fulfillment of fat requirement (% of fat requirement), natrium intake, and sleep duration were significantly associate with pre-metabolic syndrome occurrence in adolescents (p<0.05). Coefficient correlation showed positive for fat intake, % of fat requirement, and natrium intake (respectively 0.705; 0.511; 0.854) and negative for sleep duration (-0.819). Conclusion: there are association between fat intake, fulfillment of fat requirement (% of fat requirement), natrium intake, and sleep duration with pre-metabolic syndrome in adolescents. This study findings may be used as evaluation for government nutrition programs for adolescents.